2018
DOI: 10.2174/1874467211666180125163009
|View full text |Cite
|
Sign up to set email alerts
|

L-Sulforaphane Confers Protection Against Oxidative Stress in an In Vitro Model of Age-Related Macular Degeneration

Abstract: This study supports the use of L-Sulforaphane to promote regeneration of retinal cells under oxidative stress conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 0 publications
2
14
0
Order By: Relevance
“…Sulforaphane protects mouse retina from ultraviolet light by upregulating the expression of thioredoxin, an antioxidant protein whose expression is driven by Nrf2. Moreover, sulforaphane exerted protection of ARPE-19 cell line exposed to 400 μM H 2 O 2 by up-regulating the translation of thioredoxin and Nrf2 ( Tanito et al, 2005 ) and has been suggested to promote regeneration of retinal cells ( Dulull et al, 2018 ). Recently the protective effect of sulforaphane on RPE cells was correlated with preventing mitochondrial fission independently of Nrf2 activation ( O’Mealey et al, 2017 ).…”
Section: Nrf2 Activating Compounds In Amd Therapymentioning
confidence: 99%
“…Sulforaphane protects mouse retina from ultraviolet light by upregulating the expression of thioredoxin, an antioxidant protein whose expression is driven by Nrf2. Moreover, sulforaphane exerted protection of ARPE-19 cell line exposed to 400 μM H 2 O 2 by up-regulating the translation of thioredoxin and Nrf2 ( Tanito et al, 2005 ) and has been suggested to promote regeneration of retinal cells ( Dulull et al, 2018 ). Recently the protective effect of sulforaphane on RPE cells was correlated with preventing mitochondrial fission independently of Nrf2 activation ( O’Mealey et al, 2017 ).…”
Section: Nrf2 Activating Compounds In Amd Therapymentioning
confidence: 99%
“…Spatial learning and memory dysfunction [135] Chemotherapy-induced neuropathic pain [136] Protection of granulosa cells against oxidative stress [137] Cadmium-mediated carcinogenesis [138] Oxidative stress in cultured adult cardiomyocytes [139] Protective effects of glucosinolate hydrolysis products in neurodegenerative diseases [140] Clearance of Amyloid-β and Tau protein in a mouse model of AD [141] Experimental diabetic peripheral neuropathy [142] Joint inflammation in a murine adjuvant-induced mono-arthritis [143] Protection against cognitive impairment in AD-like lesions in diabetes [144] Anti-inflammatory effect of SFN on human THP-1 macrophages in a murine AD model [145] Inhibition of oxidative stress/inflammation improves cardiac function in a Rabbit Model of Chronic Heart Failure [146] Inhibition of class IIa histone deacetylase activity [147] Apoptosis via microtubule disruption in cancer [148] Inhibition of LPS-Induced Inflammation/cytotoxicity/oxidative microglial stress [149] Down-regulation of MAPK/NF-κB signaling in LPS-activated BV-2 microglia [150] Inhibition of oxidative stress in an in vitro model of age-related macular degeneration [151] Modification of Histone H3, unpacking of chromatin, to prime defence [128] Modulation of oxidative stress and inflammation in rats with toxic hepatitis [152] Modulation of oxidative damage in lead exposed rat hippocampus [153] Table 5. Cont.…”
Section: Medical Conditions Treated With Sulphoraphanementioning
confidence: 99%
“…The culture media was further supplemented with 10% foetal calf serum (FCS; Sigma Aldrich, USA) and 1% penicillin-streptomycin 10,000 U/ml (Life Technologies, USA). The ARPE-19 cells were sustained at 37 ° C in an atmosphere of 95% air and 5% CO 2 , and phenotypic characteristics of these cells were validated in our previous publication 24 .…”
Section: Methodsmentioning
confidence: 90%
“…In 2018, our laboratory reported the ability of LSF at micro molar concentrations (3µM and 5µM) to protect human retinal pigment epithelium from cell death and promoted the regeneration of these cells under oxidative stress conditions 24 . This preliminary study involving gas chromatography mass spectrometry (GC-MS) analytical methods revealed that LSF treatment induced changes in the levels of FAs, such as nonanoic acid and 9,12,15- (Z-Z-Z)-Octodectrienoic acid, and upregulated the levels of GSTM1 gene expression 24 . However, many of these significant changes were observed with the 5µM LSF treatment.…”
Section: Introductionmentioning
confidence: 99%